Crisis Gambit of the Moncloa Pact - K. O. Telin; A. V. Polosin (Сравнительная политика, 2016)
This article discusses current crisis of the contemporary Spanish political system. Both of authors suppose, previously made pragmatic decisions aimed to consolidate Spanish society after the era of Franco had become effective only in short-term perspective and are limited to only short-term positive effect today. Contemporary Spanish society faces a problem of political renewal – both in terms of party-political structure and in terms of the constitutional and legal basis of the whole system. Authors present a complex definition of the crisis as a phenomenon of political life and discuss the concept of the political stability in terms of actual practice conditions – including the realities of Spanish society. Various components of contemporary Spanish instability (the parties’ crisis, the lack of a strategic economic vector, the problems of identity and regional policy) strictly connects to the sharp conservative belief of political actors in the constitutional grounds of the Spanish state and the Moncloa Pact behind these base.